Revisiting the Influence of Neutron Transfer Coupling on Surface Diffuseness Parameters for Carbon-Induced Fusion Reactions - Rakesh Dubey (Atoms)
The influence of neutron transfer coupling on surface diffuseness has been thoroughly investigated in the study of carbon-induced fusion reactions. Through analysis of experimental measurements using advanced coupled-channel computational frameworks, we have examined how neutron exchange processes modify nuclear interaction potentials with a particular focus on surface diffuseness parameters. The findings reveal that neutron transfer mechanisms substantially contribute to reducing surface diffuseness values, with this effect being particularly pronounced in reactions involving neutron-rich isotopic combinations. This research highlights the critical importance of incorporating neutron transfer pathways when modeling fusion cross-sections, offering valuable perspectives for subsequent investigations of nuclear reaction dynamics.